Ultrafast charge transfer and recombination dynamics at the monolayer-multilayer WSe2 homojunction revealed by time-resolved photoemission electron microscopy - Xu, Ce (2020)
Transition metal dichalcogenides (TMDs) have rapidly emerged as one of the most attractive families of two-dimensional materials due to their numerous outstanding electronic and optoelectronic properties. TMDs have layer-dependent band structures, exhibiting a dramatic transition from a direct bandgap in the monolayer (1L) to an indirect bandgap in the multilayer (NL). TMD homojunctions form when a 1L TMD interfaces with an NL TMD of the same chemical composition. Such 1L/NL TMD homojunctions are predicted to have similar properties as heterojunctions, which comprises two different TMDs. In this work, we employ time-resolved photoemission electron microscopy (TR-PEEM) to study the ultrafast carrier dynamics of a WSe2 1L/NL Type-I homojunction with high temporal (50 fs) and spatial (70 nm) resolution.